2019
DOI: 10.31234/osf.io/c4t92
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Guidance of attention by working memory is a matter of representational fidelity

Abstract: Previous research shows that a single visual working memory item can guide visual attention towards objects that match the feature held in mind, but the results are mixed as to whether this attentional guidance occurs for multiple concurrently active working memory items or not. Evidence in favor of a single-item guidance account has been taken as evidence for the structure of working memory comprising multiple distinct states where one item is prioritized over all others by being placed within a special focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…For example, a model in which the processing capacity is conceptualized as a resource that is flexibly distributed over all target representations (cf. Bays & Husain, 2008;Ma et al, 2014;Williams et al, 2019), but in an unequal way, such that one representation receives the bulk of the resource at the expense of the other, would make predictions very similar to those of the serial models. Another possibility would be a system that relies on both parallel and serial subsystems.…”
Section: Serial Versus Parallel Processingmentioning
confidence: 99%
“…For example, a model in which the processing capacity is conceptualized as a resource that is flexibly distributed over all target representations (cf. Bays & Husain, 2008;Ma et al, 2014;Williams et al, 2019), but in an unequal way, such that one representation receives the bulk of the resource at the expense of the other, would make predictions very similar to those of the serial models. Another possibility would be a system that relies on both parallel and serial subsystems.…”
Section: Serial Versus Parallel Processingmentioning
confidence: 99%
“…However, this hypothesis can hardly explain our findings because previous studies showed that the memory strength of two different colors (probed by VWM performance) was not beneficial when presenting them as an integrated object (e.g., Fougnie et al, 2010;Olson & Jiang, 2002;Wheeler & Treisman, 2002;Xu, 2002). Furthermore, previous studies tried to address the debate by focusing mainly on assessing whether and when multiple items can simultaneously interact with attention (e.g., Bahle et al, 2019;Olivers, et al, 2011;van Moorselaar, et al, 2014;Williams et al, 2019). However, our study went beyond by exploring how to increase the interaction efficiency for multiple representations and demonstrated that chunking multiple colors into a single integrated object was an effective way to enhance their ability to guide attention.…”
Section: Discussionmentioning
confidence: 77%
“…When multiple colors are represented as separate objects in VWM, these objects may compete with each other to interact with attention, resulting in a decreased ability to guide attention. This might explain why in previous studies the attentional capture effect with multiple items was not as reliable as a single item (e.g., Beck & Vickery, 2019;Hollingworth & Beck, 2016;van Moorselaar et al, 2014;Williams et al, 2019). In addition, as the object is the interactive unit between VWM and attention, the efficiency of the interaction should be mainly determined by the number of objects, instead of the number of features (even from the same dimension) or Boolean maps involved in each object.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations